A note on “Taylor–Couette flow of a generalized second grade fluid due to a constant couple” - Fetecau, C.; Awan, A. U. U.; Athar, M. (Nonlinear Analysis: Modelling and Control, 2010)
In this brief note, we show that the unsteady flow of a generalized second grade fluid due to a constant couple, as well as the similar flow of Newtonian and ordinary second grade fluids, ultimately becomes steady. For this, a new form of the exact solution for velocity is established. This solution is presented as a sum of the steady and transient components. The required time to reach the steady-state is obtained by graphical illustrations.
Keywords: constant couple; steady solution; transient solution